(untitled) (Journal of Accessibility and Design for All, 2018)
The Measure of accessibility to urban infrastructures for adults with physical disabilities was first published in 2012 and proved to have good inter-rater reliability. Yet, the format (more user-friendly) and content (updated references and labels) of this instrument needed to be improved. Therefore, a new version, now entitled Measure of Environmental Accessibility (MEA), was developed to provide professionals and individuals defending the rights of persons with disabilities with a more user-friendly, objective measure of accessibility of exterior and interior urban infrastructures for adults with mobility, visual and hearing impairments. The aim of this paper is to present the improvements made in this new version and evaluate its inter-rater reliability. This cross-sectional study for inter-rater reliability was conducted by a student in occupational therapy and a student in architecture who performed 30 MEA evaluations of public infrastructures. Inter-rater reliability was evaluated using Gwet’s AC1 statistic. Most items (71%, 626/882) had AC1 values ranging from good to excellent. Some items had lower inter-rater reliability coefficients (12%, 108/882, p-value <0.05) and a few had non-significant coefficients (6%, 52/882, p-value ≥0.05). These items are distributed unevenly in the MEA. Thus, it is impossible to predict which items are less appropriate. Another 96 items (11%) did not have a Gwet’s AC1 value since both raters did not observe the evaluated element. The MEA is a reliable accessibility measure for urban built environments. Its new content and format make it a useful tool for individuals involved in the design or renovation of the built environment to improve accessibility and, therefore, inclusion of individuals with disabilities.